Efektivitas model pembelajaran menulis reflektif-kritis terhadap pembelajaran menulis teks eksposisi siswa kelas X - Junaidi, Junaidi; Wahyuni, Sri; Werdiningsih, Dyah (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
Writing instruction in Indonesian language classrooms frequently encounters obstacles, particularly because many learners find it difficult to structure and develop ideas coherently in written form. This research investigated whether the reflective–critical writing model could effectively improve students’ ability to compose expository texts. A pre-test and post-test design was used in a quasi-experimental manner. The participants were 88 tenth-grade students who were evenly assigned to an experimental group and a control group. Instruction for the experimental group was delivered through the reflective–critical writing model, whereas the control group received traditional teaching methods, including lectures and question-and-answer activities. Data analysis was conducted using paired-sample and independent-sample t-tests, followed by an effect size calculation employing Cohen’s d. There was a substantial difference between the two groups, according to the statistical findings (p = 0.000). The experimental group demonstrated a strong effect size (d = 1.690), while the control group showed a more moderate effect (d = 0.636). These findings indicate that the reflective–critical writing model is highly effective in strengthening students’ expository writing skills. Consequently, this model is recommended for implementation in other instructional settings with comparable student profiles to promote active learning and improve overall academic achievement.